Feeling Good, but Lacking Autonomy: Closed-Mindedness on Social and Moral Issues in New Religious Movements - Buxant, Coralie (Journal of religion and health, 2008)
According to previous research, New Religious Movements (NRMs) seem to have a positive effect on the mental health of members who join NRMs with some previous affective, cognitive or other vulnerabilities. The present study investigates the other, less positive, side of the psychology of NRMs, i.e. elements that may be an obstacle to optimal development, such as rigidity and low autonomy. In comparison to non-NRM members, members of various NRMs in Belgium (N = 120) were found to be low in quest religious orientation (Altemeyer and Hunsberger, Int J Psychol Religion 2:113-133, 1992), to privilege conservation values to the detriment of openness to change values (Schwartz, Advances in experimental social psychology (vol 25, pp. 1-65). Orlando, FL: Academic Press, 1992), to show submissiveness to authority in hypothetical situations (projective measure), and to highly moralize judgments of transgression relative to conventional domains (Turiel, The development of social knowledge: Morality and social convention. Cambridge: Cambridge University Press, 1983). Discussion points out the idea that rigidity and restriction of autonomy may be the price to be paid for the structuring role NRMs play with regard to previous vulnerabilities.